Simplifikasi Project-Based Learning (PjBL) Berdiferensiasi Dalam Pembelajaran Bahasa Arab di SMP Al-Madina Wonosobo - Rifqi Aulia Rahman; Zidron Abdullah; Arina Sabila Rosyadi; Khofifah Romatul Ummah; Wirda Laila Cholizatul Muna (El-Syaker : Samarinda International Journal of Language Studies, 2024)
This research investigates the implementation of Project-Based Learning (PjBL) with the principle of differentiation in Arabic language learning at SMP Al-Madina Wonosobo. The research method used is a quasi-qualitative field study. Data were collected through interviews, observations, and documentation. The results show that teachers at SMP Al-Madina have successfully implemented PjBL by considering the language proficiency levels of students and incorporating cultural elements into projects. Structured teaching steps, adaptation of projects to students' language proficiency levels, use of relevant resources, and ongoing support for language development are key features of PjBL implementation. These findings indicate that the PjBL approach with differentiation can be an effective learning method in improving students' Arabic language skills while promoting understanding and appreciation of Arab culture. This research provides an important contribution to the development of Arabic language curriculum and project-based learning at the secondary school level.